Brain attack advances in treatment (Irvine, CA : Concept Media, 2000)
Focus on the pathophysiology, diagnosis, and treatment of patients with two types of hemorrhagic brain attack - subarachnoid and intracerebral.
[3.] Hemorrhagic stroke : treatment approaches
Keywords: Cerebrovascular Disorders -- nursing